Embedding epitaxial (blue) phosphorene in between device-compatible functional layers. Issue 39 (27th September 2019) - Grazianetti, Carlo; Faraone, Gabriele; Martella, Christian; Bonera, Emiliano; Molle, Alessandro
Abstract : Large scale epitaxial (blue) phosphorene is embedded in between two functional layers aiming at its integration into an operational device. Abstract : The newly predicted allotropic phase of phosphorus termed blue phosphorus has been recently synthesized in its two-dimensional (2D) single layer fashion via epitaxial growth on a Au(111) substrate. The large scale epitaxy and the semiconductive character with a reported bandgap of ∼1.1 eV suggest that epitaxial phosphorene might be a suitable candidate to overcome the lack of a sizeable bandgap in semimetal X-enes. In close similarity to other X-enes, like silicene, the epitaxial phosphorene shows technological issues towards possible integration into devices, such as the metallic supporting template at the bottom and oxidation under ambient conditions on the top interface of its 2D lattice. Here, we report on a detailed structural and chemical analysis of epitaxial phosphorene and a newly developed methodology to allow for easy transfer of the chemically protected epitaxial phosphorene in between amorphous Al2 O3 and thin Au(111) films grown on mica. The large scale epitaxy achieved on a portable Au(111)/mica template and the low reactivity with molecular oxygen of phosphorene pave the way for easy encapsulation of epitaxial phosphorene fostering its exploitability in devices through a versatile transfer methodology, as in the case of epitaxial silicene.